2018
DOI: 10.1007/s12648-018-1340-z
|View full text |Cite
|
Sign up to set email alerts
|

Interband and intraband transition, dynamical polarization and screening of the monolayer and bilayer silicene in low-energy tight-binding model

Abstract: We investigate the interband and intraband transition of the monolayer and AB-stacked bilayer silicene in low-energy tight-binding model under the electric field, where we focus on the dynamical polarization function, screening due to the charged impurity, and the plasmon dispersion. We obtain the logarithmically divergen polarization function within the random-phase-approximation (RPA) whose logarithmic singularities corresponds to the discontinuities of the first derivative which is at the momentum q = 2kF i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…where the scattering momentum q here is usually at the Fermi surface (i.e., q = 2k F ) where the scattering the dominant, and it's also similar to the results about the Friedel oscillation of the screened potential [51,53,29,22,52] as well as the long range spin susceptibility [54]. In Fig.10, we show the RKKY range function for the casees of T = 1 and T = 2, where we set the momentum cutoff as k c = 4.8 eV.…”
Section: Disorder Effect and The Rkky Interactionsupporting
confidence: 78%
“…where the scattering momentum q here is usually at the Fermi surface (i.e., q = 2k F ) where the scattering the dominant, and it's also similar to the results about the Friedel oscillation of the screened potential [51,53,29,22,52] as well as the long range spin susceptibility [54]. In Fig.10, we show the RKKY range function for the casees of T = 1 and T = 2, where we set the momentum cutoff as k c = 4.8 eV.…”
Section: Disorder Effect and The Rkky Interactionsupporting
confidence: 78%
“…Since most of the 2D Dirac system is unlike the QED, which, in non-relativistic case, the momentum integral is ultraviolet convergent and doesn't need the cutoff, the most of the 2D Dirac systems as we discussed need the ultraviolet cutoff Λ (i.e., the Fourier transform of the Λ r ), and we estimate the ultraviolet curoff as the bandwidth of the silicene, which is about 4.8 eV, and such estimation is valid and enough for our computation in this article [21,22,20]. While for the effective mass m which is related to both the interlayer and intralayer hopping, we use the typical value of bilayer silicene which is m = 0.298m 0 [23,24,25,26,27], while for the bilayer graphene, our results are applicable after replace the effective mass as m = 0.033m 0 [28] or m = 0.029m 0 [29]. For the 3D Dirac or Weyl system, the longitudinal susceptibility as well as the current-current correlation function is needed to taking the chiral anomaly and the monopole formed by the Weyl nodes into account. )…”
Section: Discussionmentioning
confidence: 99%
“…For the dynamical polarization of the monolayer silicene, we have discussed in the Refs. [13,9,16,17], while for the bilayer silicene which is a parabolic system the interlayer hopping t ⊥ need to be taken into account. The kink of the bilayer silicene we discuss here is the AB-stacked one which is generally more stable than the AA-stacked one [65], and the parameters are setted as: The nearest-neighbor (NN) interlayer hopping is t ⊥ = 2 eV which is much larger than the next-nearest-neighbor (NNN) interlayer one [65] and thus we consider only the NN interlayer hopping here.…”
Section: Modelmentioning
confidence: 99%
“…For band structure of moolayer silicene, the symmetry between the conduction band and the valence band will be broken in silicene by the next-nearest-neighbor (NNN) Rashba-coupling (induced by the applied perpendicular electric field) (see Refs. [9,10,11]). We found that, the static polarization of bilayer silicene could be nearly temperature-independent in adiabatically case with the large band gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation